A Test of Symmetry. - Othman, Prof.Madya Abdul Rahman; Keselman, H. J.; Wilcox, Rand R.; Fradette, Katherine; Padmanabhan, A. R. (2002)
When data are nonnormal in form classical procedures for assessing treatment group equality are prone to distortions in rates of Type I error and power to detect effects.